Revisitando a funç\~ao de reaç\~ao fiscal no Brasil pós-real: Uma abordagem de mudanças de regime - Mário Jorge Mendonça; Cláudio H. dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This article presents various econometric specifications - most notably Markov- Switching models - for the fiscal reaction function of the Brazilian consolidated public sector after the 1994 ?Real Plan?. The results reported here strongly suggest that a major structural break has happened in the Brazilian fiscal policy around the year 2000. Indeed, while the reaction of primary balance to changes in net debt appears to be weak or even null when one looks at the 2000-2007 period, the contrary happens in the (more volatile) 1995-2000 years. Our results also suggest that the primary surplus is positively correlated with output and uncorrelated with inflation in both regimes.
Keywords: H6; C22; 330; Finanzpolitik; Brasilien